The exemplary Hercules from the Renaissance to the Enlightenment and beyond - Mainz, Valérie; Stafford, Emma (Metaforms, 2020)
"The Exemplary Hercules explores the reception of the ancient Greek hero Herakles - the Roman Hercules - in European culture from the Renaissance to the Enlightenment and beyond. Each chapter considers a particular work or theme in detail, raising questions about the hero's role as model of the princely ruler, and examining how the worthiness of this exemplary type came, in time, to be subverted. The volume is one of four to be published in the Metaforms series examining the extraordinarily persistent figuring of Herakles-Hercules in western culture up to the present day, drawing together scholars from a range of disciplines to offer a unique insight into the hero's perennial, but changingly problematic, appeal. Contributors are: Ioannis Deligiannis Paul Gwynne Anne-Sophie Laruelle Annie Verbanck-Piérard Joanna Woodall Marc Bizer Russell Goulbourne Pamina Fernández Camacho Filipa Araújo Alexandra Eppinger Valerie Mainz Manuel Caballero González Tomas Macsotay"--